Dampak Pengendalian Risiko Lingkungan yang Tidak Efektif terhadap Keselamatan dan Produktivitas Kerja - Safitri Kharisma; Irsyad, Irsyad; Merika Setiawati (CV. ITTC INDONESIA, 2025)
A safe and healthy work environment is a crucial element in protecting employee safety and promoting productivity. Poor environmental risk management can lead to workplace accidents, health problems, and decreased performance. This study applies a literature review method by evaluating various scientific references, such as journal articles, research, and ISO 31000:2018 risk management guidelines, to examine the effects of weak environmental risk management on worker safety and productivity. The findings show that ineffective risk control results in an increased likelihood of physical, chemical, and biological hazards in the workplace, decreased morale and work efficiency, and increased operational costs due to health problems and infrastructure damage. The implementation of systematic risk management, routine monitoring, and increased awareness of workplace safety are key factors in reducing these impacts.